Draft Annual Plan 1980-81 Vol. I-General Reviews Uttar Pradesh - Planning Commission (Planning Commission, 1979)
From the very beginning of the planning era, the nation has been concerned as much with the distributive as with the productive aspects of the economy. Particularly since the start of the Fourth Five Year Plan, planners have been trying to formulate and implement strategies which would reduce interpersonal, inter-group, inter-regional and inter-state disparities.
Uttar Pradesh Planning Department